Evaluating the use of whalewatch data in determining killer whale (Orcinus orca) distribution patterns - Hauser , Donna D. W.; VanBlaricom , Glenn R.; Holmes , Elizabeth E.; Osborne , Richard W. (J. Cetacean Res. Manage., 2023)
Commercial whalewatching has been used as an opportunistic data source for studies of cetacean distribution, but there are few comprehensive analyses of the biases and assumptions implicit in such methodology. The goal of this study was to evaluate the use of data generated by commercial whalewatch operators using a case study of whalewatchers targeting killer whales (Orcinus orca) within Washington and British Columbia inshore waters. In this region, many whalewatch vessels work cooperatively in a small, semi-enclosed area to locate and identify well-known killer whales. To address search biases and cross-examine the accuracy in killer whale locations and pod identifications by whalewatchers, an independent field study was conducted. The whalewatch data were 91.7% accurate in locating killer whales, but only 74.1% of those sightings were correctly identified to the pod level. However, identification accuracy increased to 92.6% when errors due to sub-pod mis-identification were excluded and 96.3% when early morning (before 10:30), unknown pod sightings were also excluded. It is suggested that these data can be used to describe spatial use patterns by killer whales, with recognition of the dataset’s limitations. Results of this study indicate that examination of biases is necessary before initiating research using data generated by commercial whalewatchers, but such data sources can be effective for specific study questions if the limitations are known. Although the whalewatch situation described here is relatively unique because it targets a small, well-known population, this study presents a practical methodology for evaluating the efficiency of whalewatch vessels in detecting and identifying cetaceans. Globally, whalewatching industries are increasing in numbers and geographic scope, and capitalising on these platforms of opportunity represents potentially valuable and accurate data for studies of cetacean distribution.